KUALITAS HADIS “FARADHA ZAKAT FITRAH” STUDI KRITIK SANAD DAN MATAN HADIS - Muhammad Nasir (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2022)
This study examines the quality of the hadiths "Faradha zakat fitrah", that the hadiths explain about the obligation to pay zakat fitrah for every Muslim, both men and women, to the importance of zakat on the eve of the festival. Then the hadiths use several kinds of food that can satisfy in the form of staple foods such as dates, poetry and wheat and rice. The main focus in this research is the sanad and matan of the Hadiths of the Prophet saw which contain about "faradha zakat fitrah" this research is a library research with the main reference is the books of hadith al-Kutub al-Tis'ah (Nine Books Induk Hadith), and maktabah syamilah. In addition to the books of hadith mentioned above, books related to takhrij al-hadith are also references in this study, such as: Ushul al-Takhrij wa Dirasat al-Asanid. Research Methodology of the hadith of the Prophet written by Syuhudi Ismail, and others. To research the narrators of Hadith, used as a reference are books related to the study of the content of hadith. The result of this research is a hadith chain of authentic quality, namely the narration of Abu Dawud. From the point of view of authentic hadith, it does not contradict the Qur'an and authentic hadith, common sense, historical facts, language and the principles of Islam.